Multidimensional analysis of courtyard building environmental performance using computational fluid dynamics - Sun, Hao (2024)
Courtyards are important for enhancing natural ventilation and daylight while mitigating extreme heat in urban environments. However, their interaction with courtyards’ indoor spaces and the impact of passive technologies such as different roof designs, vegetation, and water sprayers on indoor aerothermal conditions and pollutant transmission has not been studied. To address research gaps, this study explores natural ventilation, temperature control, and pollutant transmission in courtyard buildings using CFD simulations. We validate different courtyard models derived from wind tunnel experiments, comparing various turbulence models—specifically the Reynolds-Averaged Navier-Stokes (RANS) models, including k-epsilon and k-omega—to ensure robust CFD model validation. This study examines ten different roof designs' impact on natural ventilation and passive cooling in courtyard buildings. Results show that dome roofs enhance ventilation, increasing indoor wind speed by 80% and reducing temperatures by up to 2.1°C compared to flat roofs. Integrated vegetation, particularly large trees, significantly improves aero-thermal comfort, with temperature drops up to 6.58°C. Additionally, water sprays in single-sided ventilated courtyards improve indoor thermal conditions, lowering temperatures by 2.06°C and increasing humidity by 4.29%. Pollutant dispersion analysis reveals that structure, orientation, and external wind patterns significantly influence pollutant spread, primarily affecting adjacent rooms on the same floor. This multidimensional analysis focuses on courtyard design features and their impact on indoor environments, evaluating passive technologies like vegetation and water features in improving microclimates. It provides insights into design choices and air quality, promoting sustainable architectural practices to address climate change and create healthier urban living spaces.